0
$\begingroup$

Show that the equation $z=a+2bt+ct^2$ represents a parabola where $a,b,c\in\mathbb{C}$.

My approach: let $a=m+m'i, b=l+l'i, c=n+n'i, z=x+yi$.

Equating real and imaginary parts on both sides, we get $$x=m+2lt+nt^2 ,y=m'+2n't+n't^2$$ since these are quadratic equations in $t, i$ have compared both the equations and getting straight line as locus but i have to show parabola. please help

$\endgroup$
1
$\begingroup$

Translate the origin of the complex plane by $a$ and define $s\equiv z-a$, your new complex variable in your new coordinate system that is just translation of the old one by $a$:

$z-a\equiv s=2 b t+c t^2$

Let $\Re(s)=x$ and $\Im(s)=y$. Thus, with obvious notation,

$x=2b_x t+c_x t^2$

$y=2b_y t +c_y t^2$

Your goal is now to rigidly rotate the $s$-plane so that $x$ becomes function of $t$ alone, without $t^2$ in it. Then $x$ itself is variable $t$, just like in Cartesian system.

Rotation is done by multiplying by $e^{i\phi}$ with some fixed constant $\phi$. Proof: $se^{i\phi}=re^{i\alpha}e^{i\phi}=re^{i(\alpha+\phi)}$. So everything is rotated by angle $\phi$ about the origin.

So multiply $s=x+iy$ by some $\cos\phi+i\sin\phi$, the result reads $s'=x\cos\phi-y\sin\phi + i (y\cos\phi+x\sin\phi)$. Hence,

$x'= 2b_x t\cos\phi+c_x t^2\cos\phi-2b_y t\sin\phi-c_y t^2\sin\phi$

$y'=2b_y t\cos\phi+c_y t^2\cos\phi+2b_x t \sin\phi+c_x t^2\sin\phi$

Terms with $t^2$ disappear from $x$ if you choose to use angle of rotation $\phi$ such that

$c_x\cos\phi=c_y\sin\phi$

or equivalently

$c_y=c_x \cot\phi$

Do notice that $\cot\phi=c_y/c_x$ and so is neither $0$ nor $\infty$ if $c_x\ne 0$ and $c_y\ne 0$. Hence both sine and cosine do not vanish.

Then

$x'= 2t(b_x \cos\phi-2b_y \sin\phi)$

$y'=2b_yt\cos\phi+c_x t^2 \cos^2\phi/\sin\phi+2b_x t \sin\phi+c_x t^2\sin\phi=\\ 2t(b_y\cos\phi+b_x \sin\phi)+c_x t^2 \sin\phi$

Hence $y'$ is quadratic in $t$ whilst $x'$ is only linear in $t$. It's parabola alright.

$\endgroup$
  • $\begingroup$ Is there any flaw in my approach as i have stated in question $\endgroup$ – Siddhartha Raja Jun 17 '18 at 5:45
  • $\begingroup$ no, no flaw, you just have to push on, you got first two equations. $\endgroup$ – anonymous Jun 17 '18 at 5:47

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.